Enhancing the safety of underwater subway tunnels through grouting reinforcement in fault fracture zones - Hui Zhang; Majed A.A. Aldahdooh; Yong Hui Shang; Hang Yin; Mohammed J.K. Bashir; Ai Wei Wong; Abdullateef Ashola Olanrewaju; Choon Aun Ng (Results in Engineering)
Subsea fault fracture zones pose significant stability challenges and heighten the risk of tunnel face collapse and sudden water inrush during subway construction. Despite the common practice of using grouting reinforcement to stabilize the surrounding rock, there is limited research on its specific control effects. This study addresses this gap by investigating the impact of grouting reinforcement on the safety of subsea tunnels crossing fault fracture zones, using the Qingdao subway project in China as a case study. A coupled numerical model encompassing seepage, stress, and displacement fields was developed via MIDAS/GTS to analyze changes in porewater pressure, seepage velocity, surrounding rock stress, initial support stress, and tunnel displacement before and after grouting. The results demonstrate a significant reduction in porewater pressure and stress concentration post-grouting. The maximum and minimum principal stresses of the initial support were approximately 4.7 MPa and 3.4 MPa, which were found to be within safe limits, indicating a well-designed reinforcement strategy. Additionally, settlement and uplift measurements were 12 mm and 14 mm, representing a 54 % reduction compared to conditions without grouting reinforcement. Both maximum settlement and uplift values were considerably below standard limits of 20 mm, affirming the effectiveness of the grouting measures. The close alignment between field test data and numerical model results validates the model's accuracy. This study provides critical insights and a scientific basis for evaluating and implementing grouting reinforcement in similar subsea tunnel projects, contributing to safer and more efficient construction practices.